Trends of development of adult edcation in the eu countries - Samoilenko, Oksana; Dubaseniuk, Oleksandra; Sydorchuk, Ninel (My University, 2019)
The article is devoted to modern tendencies of adult education. At the beginning of the XXI century, the concept of continuing education was actively being implemented in the countries of the European Union. The acquired knowledge throughout life enhances the prospects of adults in the labor market, improves the quality of human capital of the economy, helps them to adapt more quickly to social change, promote self-realization of the individual. The purpose of the study is to characterize trends in the development of adult education in the member states of the European Union.The significant increase in the number of adults participating in various forms of education within the formal education system and beyond confirms the need for adult education by European states, international and national organizations, and non-governmental organizations. Adult education is a fundamental factor in European development and the competitiveness of countries. Methodology of Research. Scientific research was carried out with the use of comparative pedagogical methods, among which the leading role played: the method of studying documentary and scientific and pedagogical sources, the method of interpreting educational facts, the method of analysis of foreign sources, the method of analysis of mass phenomena, which was implemented in the study to highlight the main trends in the development of education adults in EU member states. As a result of the increasing availability of education, processes of internationalization, globalization and transboundary educational migration take place. This leads to the universalization of knowledge, the emergence of international quality standards and the development of the innovative nature of higher education, the expansion and strengthening of international cooperation, the enhancement of academic and student mobility, and others. Studying foreign students also affects the development of the country of origin, contributes to the global economic and political stability of the EU member states. На початку XXI століття в країнах Європейського Союзу активно впроваджувалася концепція неперервної освіти. Набуті знання протягом усього життя підвищують перспективи дорослих на ринку праці, покращують якість людського капіталу економіки, допомагають їм швидше адаптуватися до соціальних змін, сприяють самореалізації особистості. Мета дослідження: загальна характеристика тенденцій розвитку освіти дорослих у країнах-членах Європейського Союзу. Наукові дослідження проводилися з використанням порівняльних педагогічних методів, серед яких відігравала провідну роль: метод вивчення документальних та науково-педагогічних джерел, метод інтерпретації навчальних фактів та метод аналізу зарубіжних джерел. Результат. У наслідку зростаючої доступності освіти відбуваються процеси інтернаціоналізації, глобалізації та транскордонної освітньої міграції.
Keywords: adult education; освіта дорослих; internationalization; globalization; transboundary education; інтернаціоналізація; глобалізація; трансгранична освіта; академічна мобільність